Wetland Plants and their Local Uses: Observations from Rampur Ghol, Chitwan, Nepal - Dangol, Dharmqa Raj; Gautam, Birendra; Oli, Bam Bahadur (Journal of Natural History Museum, 2015)
This paper is based on the study of wetland plant resources of Rampur Ghol conducted from 2012 to 2014. This paper documents 117 plant species belonging to 39 families and 92 genera in the area. Dicot species (60 spp.) dominated over the monocots (53 spp.) and pteridophytes (4 spp.). The dominant family was the Poaceae (21 spp.) followed by Cyperaceae (14 spp.), Asteraceae (10 spp.), Scrophulariaceae (8 spp.), Polygonaceae (5 spp.)and Acanthaceae (4 spp.). By life form, emergent species were highest (86%) compared to submerged (6%), rooted floating leaved plants (6%) and free floating plants (2%). These plants had use value of medicine, food (for human, domestic animals, and fish), fuel energy, artifacts, etc. Realizing its contribution along with useful plants, Rampur Ghol area should be conserved for learning and recreation purposes. J. Nat. Hist. Mus. Vol. 28, 2014: 142-159